2021
DOI: 10.1007/s12024-021-00414-9
|View full text |Cite|
|
Sign up to set email alerts
|

Cytokine storm and histopathological findings in 60 cases of COVID-19-related death: from viral load research to immunohistochemical quantification of major players IL-1β, IL-6, IL-15 and TNF-α

Abstract: This study involves the histological analysis of samples taken during autopsies in cases of COVID-19 related death to evaluate the inflammatory cytokine response and the tissue localization of the virus in various organs. In all the selected cases, SARS-CoV-2 RT-PCR on swabs collected from the upper (nasopharynx and oropharynx) and/or the lower respiratory (trachea and primary bronchi) tracts were positive. Tissue localization of SARS-CoV-2 was detected using antibodies against the nucleoprotein and the spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 116 publications
2
56
1
8
Order By: Relevance
“…The results obtained certainly provide indications for the identification of operating methods capable of limiting the spread of pathogenic microorganisms in the work environment and minimizing the biological risk [48][49][50]. The performance of monitoring activities made it possible to characterize the different sources of risk, including new ones, to which the different operators are exposed [51].…”
Section: Discussionmentioning
confidence: 94%
“…The results obtained certainly provide indications for the identification of operating methods capable of limiting the spread of pathogenic microorganisms in the work environment and minimizing the biological risk [48][49][50]. The performance of monitoring activities made it possible to characterize the different sources of risk, including new ones, to which the different operators are exposed [51].…”
Section: Discussionmentioning
confidence: 94%
“…This finding supports the hypothesis of Huang JL et al [27], who stated that the SARS-CoV-2 virus directly or indirectly destructs the CD8 (+) T lymphocytes through impairment of cellular immunity or SARS-CoV-2 induced-mediators, but the mechanism is not clear yet. However, an immunohistochemical study by Frisoni P et al [24] reported that CD8 (+) T cells and CD20 (+) B cells were mainly found in the lung. They showed that the reason for this was that none of the patients in their study had received any treatment that would activate the immune system, for they died in an out-of-hospital setting [24].…”
Section: Discussionmentioning
confidence: 98%
“…However, an immunohistochemical study by Frisoni P et al [24] reported that CD8 (+) T cells and CD20 (+) B cells were mainly found in the lung. They showed that the reason for this was that none of the patients in their study had received any treatment that would activate the immune system, for they died in an out-of-hospital setting [24]. In our study, 45.7% (n=43) of the cases were hospitalized.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The prevention or attenuation of the cytokine storm and endothelial cell activation may be helpful to mitigate cardiac involvement [55]. Indeed, a better understanding of cardiac involvement pathophysiology and the pathological pattern is needed and autoptic studies on COVID-19 deaths should be further promoted [13,56].…”
Section: Discussionmentioning
confidence: 99%